Buprenorphine discontinuation and utilization of psychosocial services: a national study in the Veterans Health Administration - Emma N. Cleary; Angela L. Rollins; Alan B. McGuire; Laura J. Myers; Patrick D. Quinn (Addiction Science & Clinical Practice)
Abstract Background Longer duration of treatment with medication for opioid use disorder (MOUD) is associated with improved outcomes, but long-term retention remains a challenge. Research is needed to identify psychosocial interventions that support MOUD retention. To address this gap, we examined associations between a wide range of psychosocial services and buprenorphine treatment discontinuation across 18 months among a large cohort of Veterans initiating buprenorphine nationwide. Methods We identified a cohort of patients with new buprenorphine initiation in 2017–2018 in Veterans Health Administration electronic health record data (N = 11,704). We examined prescription fills for up to 18 months after initiation. The primary outcome was first discontinuation of buprenorphine. We examined a variety of services, including psychotherapy in specialty substance use disorder (SUD) and mental health clinics, other healthcare services, and residential programs. To examine time-varying associations between psychosocial services and risk of discontinuation, we fit extended Cox regression models for each service separately and simultaneously. Results Overall, 80.5% of patients discontinued buprenorphine at least once within 18 months. Risk of discontinuation was 18% (HR: 0.82, 95% CI: 0.77, 0.87) relatively lower following SUD psychotherapy and 26% (HR: 1.26, 95% CI: 1.15,1.39) higher following residential treatment. Conclusions Several services, including residential treatment, were associated with greater risk of subsequent buprenorphine discontinuation, whereas only SUD psychotherapy was consistently associated with lower risk of later discontinuation. These findings emphasize the need for future studies to increase understandings of beneficial and disruptive components of psychosocial services to improve treatment retention among patients receiving MOUD.